Country Partnership Framework for Montenegro for the Period FY16-FY20 - World Bank (World Bank, Washington, DC, 2016)
The Country Partnership Framework (CPF) for Montene gro covers the period from July 1, 2015 to June 30, 2020 (fiscal years 2016-2020). This CPF builds on the results and lessons of the previous World Bank Group (WBG) Country Partnership Strategy (CPS), which originally covered the period July 1, 2011 to June 30, 2014, and was subsequently extended to June 30, 2015.The one-year CPS) extension was intended to provide greater clarity on the country’s medium-term macro-fiscal framework as a basis for the new CPF, and to give additional time to make progress on improving environmental management, a key pillar of the CPS. The new CPF seeks to address the top priorities identified by the recently completed Systematic Country Diagnostic (SCD) as those that Montenegro needs to most urgently tackle to advance in its path towards shared prosperity and sustainable development. The CPF will selectively support Montenegro’s development agenda outlined in the Montenegro Development Directions (MDD) 2015-2018, Economic Reform program (ERP) 2015-2017 and the Montenegro European Union (EU) Accession Program 2014-17. The WBG strategy will continue to support, and be aligned with, Montenegro’s EU accession and integration process. The formulation of the new CPF benefitted from extensive consultations held in October 2015 and in January and March 2016, and involving several line ministries, municipalities, civil society, academia, and private sector across various regions of the country, as well as representatives of the international development community. The resulting proposal for engagement under the FY16-20 CPF reflects a broad consensus of a wide range of stakeholders and a shared understanding of development priorities and challenges facing the country.